High-speed line-scan confocal Raman microscope with enhanced diffraction efficiency. (15th November 2019) - Xing, Jingchao; Kang, Sung-Hoon; Choi, Young-Man; Lee, Seungwoo; Yoo, Hongki
Abstract: Confocal Raman microscopy is commonly employed across different research fields because it allows for label-free sample investigation at high spatial resolution. However, the slow data acquisition speed of Raman microscopy limits its application for imaging large area samples. We developed a line-scan confocal Raman microscope to achieve parallel detection for high-speed data acquisition and proposed a dual mirror scan method to enhance the diffraction efficiency of the spectrometer. We used a Powell lens for the line illumination and demonstrated that it can provide a more uniform intensity distribution than a cylindrical lens. The spectrometer consists of a volume phase holographic grating and two scanning mirrors. Using the proposed dual mirror scan method can provide a high-resolution Raman spectrum at high efficiency over a wide spectral range. The system has a maximum spectral rate of 25 600 spectra s −1 and a theoretical spectral resolution of 1.2 cm −1 . With the parallel detection by the line illumination and the enhanced diffraction efficiency, we expect the proposed system can be used in a variety of applications that require a high spectral rate, such as wide-field Raman imaging.